2011
DOI: 10.1007/s00442-011-2053-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prescribed fire, supplemental feeding, and mammalian predator exclusion on hispid cotton rat populations

Abstract: Predation and food resources can strongly affect small mammal population dynamics directly by altering vital rates or indirectly by influencing behaviors. Fire may also strongly influence population dynamics of species inhabiting fire-adapted habitats because fire can alter food and cover availability. We used capture-mark-recapture and radio-telemetry studies to experimentally examine how supplemental feeding, mammalian predator exclusion, and prescribed fire affected survival, abundance, and reproduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 34 publications
1
46
2
1
Order By: Relevance
“…grahamensis (Koprowski et al 2006). Recent experimental work has shown that increased predation was responsible for a reduction in survival of cotton mice Peromyscus gossypinus due to the removal of ground cover by fire (Morris et al 2010, Morris et al 2011. The results of the current analysis from Australia's tropical savannas indicate that northern brown bandicoot survival decreased in higher intensity fires, and this decline was gradual rather than sudden after the application of the experimental fires.…”
Section: Discussionmentioning
confidence: 70%
“…grahamensis (Koprowski et al 2006). Recent experimental work has shown that increased predation was responsible for a reduction in survival of cotton mice Peromyscus gossypinus due to the removal of ground cover by fire (Morris et al 2010, Morris et al 2011. The results of the current analysis from Australia's tropical savannas indicate that northern brown bandicoot survival decreased in higher intensity fires, and this decline was gradual rather than sudden after the application of the experimental fires.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, frequent use of prescribed fire in longleaf pine forests increases understory plant species richness, diversity, and evenness (Brockway and Lewis 1997), which may influence where bobcats search for prey items. Small mammals (e.g., cotton rats [Sigmodon hispidus], Conner et al 2011, Morris et al 2011 are commonly exposed to predation from bobcats and other predators following a fire event due to reductions in herbaceous cover. Our results may also be due to the scale of fire relative to bobcat home ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Bobcats selected mature pine and mature pine-hardwood stands managed by frequent fire, but also selected other habitat types such as agricultural fields and shrub-scrub. Additionally, fire events facilitate predation of small mammal communities by temporarily reducing cover and exposing prey to predators , Morris et al 2011. Therefore, there is a chance that bobcats-and other predators-may be temporarily attracted to recently burned areas, suggesting a tradeoff between managing for prey that may be particularly sensitive to predators following fire (e.g., wild turkey nests) and those species that rely on frequent fire (e.g., gopher tortoise [Gopherus Polyphemus and red-cockaded woodpecker (Picoides borealis; Alavalapati et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cotton rats start breeding as early as 2 months of age, and few survive >6 months (Odum, 1955). Cotton rats are an important prey species for a variety of predators and the primary cause of mortality is predation (Cameron and Spencer, 1981;Morris et al, 2011a). Cotton rats are characterized by high fecundity rates and their prolific breeding coupled with substantial predation mortality leads to population turnover in 5-8 months (Goertz, 1964).…”
Section: Study Speciesmentioning
confidence: 99%